Development and application of a high throughput one-pot extraction protocol for quantitative LC-MS/MS analysis of phospholipids in serum and lipoprotein fractions in normolipidemic and dyslipidemic subjects - Gardner, Michael S.; Kuklenyik, Zsuzsanna; Lehtikoski, Antony; Carter, Kayla A.; McWilliams, Lisa G.; Kusovschi, Jennifer; Bierbaum, Kevin; Jones, Jeffrey I.; Rees, Jon; Reis, Gregory; Pirkle, James L.; Barr, John R. (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2019)
Progress toward better diagnosis and treatment of lipid metabolism-related diseases requires high throughput approaches for multiplexed quantitative analysis of structurally diverse lipids, including phospholipids (PLs). This work demonstrates a simplified “one-pot” phospholipid extraction protocol, as an alternative to conventional liquid-liquid extraction. Performed in a 96-well format, the extraction was coupled with high throughput UPLC and multiplexed tandem mass spectrometry (MS/MS) detection, allowing non-targeted quantification of phosphatidylcholines (PC), sphingomyelins (SM), lysophosphatidylcholines (LPC), phosphatidylethanolamines (PE), and phosphatidylinositols (PI). Using 50 μL aliquots of serum samples from 110 individuals, lipoproteins were fractionated by size, and analyzed for phospholipids and non-polar lipids including free cholesterol (FC), cholesteryl esters (CEs) and triglycerides (TGs). Analysis of serum samples with wide range of Total-TG levels showed significant differences in PL composition. The correlations of molar ratios in lipoprotein size fractions, SM/PL with FC/PL, PE/PL with TG/CE, and PE/PL with PI/PL, demonstrate the applicability of the method for quantitative composition analysis of high, low and very-low density lipoproteins (HDL, LDL and VLDL), and characterization of lipid metabolism related disease states. •A high-throughput method for measuring 5 phospholipid class totals is presented.•The method utilizes a “one-pot” extraction and 3 min UHPLC-MS/MS analysis.•The method requires only 0.2 μL of whole serum/plasma or 20 μL of fractionated sample.•Relative assessment of PL species composition is also demonstrated.•Whole and size-fractionated data from 100 individuals is presented.